2013
DOI: 10.1002/srin.201300013
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Evolution of Inclusions in Ti‐Bearing Al‐Deoxidized Molten Irons at 1873 K

Abstract: To study the evolution of inclusions in Ti‐bearing Al‐deoxidized steel, four types of molten irons with different Al and Ti contents were prepared. Subsequently, scanning electron microscope (SEM) and high‐temperature confocal scanning laser microscope (CSLM) were used to investigate the dynamic process of inclusions in the samples. The CSLM showed that Al2O3 inclusions strongly attracted each other and agglomerated easily. In high‐Al and high‐Ti melt, although inclusion clusters were frequently observed, its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The stability phase diagram of oxides in the Fe–Al–Ti–O system at 1873 K is obtained was presented by Matsuura et. al., as is shown in Figure . The equilibrium calculation results of the inclusion precipitations predicted by using Thermo‐Calc were also inserted.…”
Section: Discussionmentioning
confidence: 68%
“…The stability phase diagram of oxides in the Fe–Al–Ti–O system at 1873 K is obtained was presented by Matsuura et. al., as is shown in Figure . The equilibrium calculation results of the inclusion precipitations predicted by using Thermo‐Calc were also inserted.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, the presence of Ti oxides during the transient stages after Ti addition was reported by previous studies by Masuura et al [20] and Wang et al [34,35]. Aside from the traditional metallographic characterization of Al-Ti-O inclusion behaviors by investigating the two-dimensional features, various methods including the focused-ion-beam method [43], confocal scanning laser microscopy [37], and electrolytic extraction [33] have been adopted to investigate the inclusion behaviors in Al-killed Ti-bearing steels. However, the existing literature on the transient products has suffered from a lack of direct and systematic descriptions of the three-dimensional features of temporary titanium oxide inclusions during the transient stages after Ti addition, especially when they were associated with existing alumina; thus, the effect of the existing Al 2 O 3 morphology on transient reactions after Ti addition has so far been unclear.…”
Section: Introductionmentioning
confidence: 93%
“…Second, although various factors including the sequence of alloy addition [18,20,32,33], titanium source [34], titanium/aluminum ratio [35], and element contents [19,[36][37][38][39] have been examined their impacts on the inclusion behaviors during Al and Ti additions, several fundamental questions remain about the evolution mechanism of the inclusion behaviors. In a laboratory study of deoxidation by Al and Ti at 1873 K, Nagata et al [40] found that alumina particles were formed with an acicular shape at first and gradually changed to clusters of granular Al 2 O 3 spheres, but the inclusion characteristics were, nevertheless, not significantly affected by the subsequent Ti feeding.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the particle characteristics can be modified by the addition of deoxidizing alloy. It has been reported that the Al–Ti oxide exists in Al–Ti deoxidized steel . With Ca or Ce treatment, the inclusions in Al–Ti deoxidized steel are changed to Ca–Al oxides with a layer of TiN in Ca‐bearing steel or CeAlO 3 inclusion in Ce‐bearing steel, respectively.…”
Section: Discussionmentioning
confidence: 99%